Fulfilling the Transfer Mission at an Urban Technical College: How a Transfer Center Mediates Baccalaureate Aspirations for Students. Issue 12 (2nd December 2018) - Felix, Eric R.; Trinidad, Adrián
ABSTRACT: This article examines transfer center practices at a historically vocational community college to understand how transfer to four-year institutions happens. By focusing on the transfer center, this study explores the practices that could support transfer goals in a vocational and technical environment. Drawing on concepts of organizational culture, we framed the 'invisible' factors that impact transfer practices and outcomes. An ethnographic case study approach was used to gather over 70 hours of observations and interviews with staff, faculty, and senior administration. This data were analyzed to assess how transfer practices supporting baccalaureate-aspiring students were shaped by a vocationally dominant environment. The experiences and practices of those responsible for the transfer center are highlighted. Results indicate that the culture of trades at the campus constrained the transfer resources available to the center, which led to an adaptation of trade-oriented practices by center staff, and ultimately, an attempt to preserve the transfer purpose for those seeking four-year institution. This study contributes to a paucity of research that examines transfer in historically technical community colleges, particularly in a transfer center setting.